Pengaruh Kualitas Pelayanan, Promosi, Dan Citra Perusahaan Terhadap Keputusan Penggunaan Jasa Pada PT. Pos Indonesia Cabang Kediri - Herlinda Putri Wuryantari; Miftahul Munir; Agung Pambudi Maha Putra (Journal of Creative Student Research, 2023)
This research aims to determine the influence of service quality, promotion and company image on decisions to use services at PT. Pos Indonesia Kediri Branch partially and simultaneously. This research uses quantitative methods where the population studied is all consumers who have used PT services. Pos Indonesia Kediri Branch within a 2 month period. The number of samples taken was 92 respondents using a non-probability sampling method, namely accidental sampling. Data collection uses a questionnaire. The research results show that (1) service quality has a positive and significant effect on the decision to use services with a t value of 2.224 and a sig value. 0.029 < 0.05; (2) promotion has a positive and significant effect on the decision to use services with a t value of 7.128 and a sig value. 0.000 < 0.05; (3) company image has a positive and significant effect on the decision to use services with a t value of 2.051 and a sig value. 0.043 < 0.05; (4) service quality, promotion and company image simultaneously have a positive and significant effect on the decision to use services with an F value of 22.930 and a sig value. 0.000 < 0.05. Decision to use services at PT. Pos Indonesia Kediri Branch is influenced by these three variables by 43.9%, while the rest is influenced by other factors not mentioned in this research.